Aplikasi Absensi Mahasiswa Kerja Praktik Menggunakan QR Code Berbasis Android - Alda, Muhamad; Juarsyah, Muhammad; Nugraha, Akbar; Alfachry, Louliq Rifky (Jurnal Manajemen Informatika JAMIKA, 2024)
Practical Work Activities carried out in the Information Systems Study Program at the Faculty of Science and Technology State Islamic University of North Sumatra still carry out the semi-manual attendance recording process. This process is done semi-manually using paper and then entered into Microsoft Excel. This makes the process of processing student attendance data considered less effective and efficient. This is due to the fact that it is difficult to send student attendance data to those who need it and that the data is only stored on a particular computer device. The purpose of this research is to create an android-based application that can be used by the Information Systems study program to process student attendance data and facilitate the distribution of attendance data. This research uses waterfall approach for system development. Includes the stages of Communication, Planning, Modeling, Construction, and Deployment. On the other hand, the system testing method uses the black box testing method. This application is created with a codular framework and spreadsheet database, and can be accessed through android devices and accessed online. The result of this research is in the form of an application that can conduct student practical work attendance and provide report recaps to the study program. This application helps information system study program operators process student attendance data by adding data and facilitating the distribution of attendance data.